The Scenarios for Sustainability of Vannamei (Litopenaeus vannamei) Aquaculture Through Environmental Management Accounting - Utami, Tiwi Nurjannati; Mulyanto; Wardhani, Niken Hendrakusma; Setijawati, Dwi; Iranawati, Feny; Lelono, Tri Djoko; Harlyan, Ledhyane Ika; Agustin, Rizky Fadilla (HABITAT, 2025)
There is increasing awareness of the importance of sustainability in aquaculture, however, research that explicitly integrates accounting with environmental information in decision-making remains relatively unexplored. Sumenep Regency in East Java is one of the largest producers of vannamei shrimp with high economic value. This research was conducted at a vannamei shrimp farming company in the area. This company uses a semi-intensive system and has made efforts to care for the environment, but has not fully integrated environmental aspects into its financial support. It has the potential to hurt sustainability. Environmental management accounting is an accounting approach that integrates environmental information into the company's accounting system, to support better decision-making in terms of environmental and economic performance. This study aims to design a scenario for the sustainability of aquaculture vanname shrimp (Litopenaeus vannamei) business through environmental management accounting in the company Sumenep Regency. The data are collected through interviews, observation, and documentation. It employs prospective analysis of SMIC-Prob based on probability with subjective probability. It is used to compute the probability of the event. This study uses probability sampling. The experts are top manager, middle managers in production and finance, local government, and researchers in fishery agribusiness. This study shows that the primary scenario recommendation for the sustainability of vanname shrimp farming is integrated environmental management in accounting. Meanwhile, the government needs to support them to apply it through socialization, regulation, and educating/training about it.